Light Switch: Towards a History of the Second Enlightenment - Nelles, Henry (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2014)
This paper attempts to answer the question how and why did planet Earth begin to glow in the dark over the long twentieth century? It begins with a survey of the contemporary global distribution of light followed by an excursion into the history of night, early efforts at interior and exterior illumination, and the global diffusion of light and power companies aided by foreign investment. The spread of the automobile vastly expanded the market for nocturnal illumination just as the economies of scale associated with electricity generation drove down the unit cost of lumens. The paper concludes by emphasizing light as a form of human cultural expression by stressing the importance of social systems, political and cultural factors in turning the lights on, and off.